Are German coaches highly exhausted? A study of differences in personal and environmental factors - Altfeld, S.; Kellmann, M.; Curran, T. (International Journal of Sports Science and Coaching, 2015)
Previous research has produced equivocal findings in regard to personal and environmental parameters influencing coaches' perceptions of stress and burnout levels. Moreover, there is a paucity of studies examining these factors in European professional sport contexts. This study investigated the influence of person-related (e.g., age, hours per week, level of recovery, coaching alternatives, experience as an assistant), sport-related (e.g., type of sport, working in youth or senior section, level of performing), and perception-related variables (e.g., feeling of meaningfulness, financial security) in relation to burnout of German full-time coaches. One-hundred and fifty eight coaches of different sports and levels completed a demographical survey, a German coaches' version of the Maslach Burnout Inventory, and the Recovery-Stress Questionnaire for Coaches. Two contrasting groups were formed to compare coaches with the lowest scores in Emotional Exhaustion (lowest 20%) and the highest scores in Emotional Exhaustion (highest 20%). Overall Stress (â = 3.92, p < .001) and Overall Recovery (â = -2.86, p < .001) demonstrated significant effects on Emotional Exhaustion within multiple regression analysis. Moreover, the variables sense of well-being (r = -.46, p < .001), feeling of meaningfulness (r = -.28, p < .001) showed significant relationships to the key burnout symptom of Emotional Exhaustion. The extreme group comparison indicated significant differences in person-related and perception-related parameters. Recovery as well as social support might be important in managing stress in the challenging work environments of full-time coaches. Additionally, the perception of the current coaching job might be more important than context-related variables (e.g., type of sport, level). ABSTRACT FROM AUTHOR